Playwrights and Copyright - Wright, Doug (The Columbia Journal of Law & the Arts, 2015)
Broadway, 1926. The Rialto is alive with drama. At the Mansfield Theater, a revival of the Pulitzer Prize-winning play Beyond the Horizon is enjoying a healthy run. At the Imperial, George Gershwin’s Prohibition romp Oh, Kay is a bona fide sell-out. At the Mayfair, an unexpected guest upstages the opening night of a searing marital tragedy entitled The Half- Naked Truth. In the words of critic Brooks Atkinson: Toward the end of the second act. . .a gray cat walked amiably across the stage, peeped curiously over the footlights, and then sat down comfortably, yawned a little, blinked sleepily and apparently settled for the night. . . . . .What drama could vie with the reality of a cat? Or what actor could put a cat to shame?. . . . . .Unfortunately. . .the play. . .was amateurish in every [other] respect. The Half-Naked Truth closed within a month; the fate of the cat remains unknown. But the dramas playing out on Broadway that fateful year aren’t all happening onstage; in a nearby office building behind closed doors, a cluster of playwrights- Eugene O’Neill and humorist George Kaufman among them-are meeting with a group of theatrical producers. The writers have recently established a Guild, just fourteen years old, to fight for equitable practices in their profession. Somewhat reluctantly, the producers have agreed to meet with them. On one point, the Guild is intractable: the right of its members to control their copyrights and prevent unauthorized changes in their scripts.